Coronary perivascular inflammation in type 2 diabetes mellitus patients: the missing piece in the puzzle of their increased cardiovascular risk?. (14th October 2021) - Cecere, A; De Kreutzenberg, S; Motta, R; Benvenuti, F; Iliceto, S; Avogaro, A; Tona, F
Abstract: Background: Coronary atherosclerosis is a frequent complication of type 2 diabetes mellitus (DM2). Considering the contiguity with the vascular wall, perivascular adipose tissue (PVAT) could play a crucial role in the pathogenic microenvironment of atherosclerosis. The PVAT attenuation index (p-FAI) is a non-invasive marker that reveals the change in peri-coronary adipose tissue (PCAT). High values of p-FAI are associated with increased cardiovascular mortality and poor prognosis. Emerging as an indication, contributor to, and therapeutic target for atherosclerosis, PCAT warrants further investigation in DM2. Purpose: We aimed to characterize the association of PCAT by p-FAI and DM2, and to compare coronary inflammation in DM2 versus non DM2 patients with coronary artery disease (CAD), and versus healthy controls. Methods: 15 consecutive DM2 patients (9 male, age 63±10 years) without symptoms/signs of cardiovascular disease were included in the study and compared to 8 non DM2 patients with CAD and 13 healthy volunteers without cardiovascular diseases, matched for age and sex. All patients and controls underwent coronary computed tomography angiography (CCTA) for the evaluation of coronary arteries and p-FAI. All scans were performed using a 320-slice multidetector computed tomography (Toshiba Aquilion) and a prospective ECG-triggered sequential acquisition. p-FAI analysis was performed using a dedicated workstation (Aquarius iNtuition Edition version 4.4.13. P3; TeraRecon Inc., Foster City, CA, USA). The proximal 40-mm segment of the right coronary artery (RCA) was identified and the inner and the outer wall were automatically traced, excluding the 10 mm from the ostium. The adipose tissue localized within a radial distance from the outer wall equal to a medium diameter of the RCA was evaluated. Voxel histograms of CT attenuation were traced and included between −190 to −30 HU within the PCAT volume. p-FAI was calculated as the median CT attenuation value of PCAT of the proximal 40-mm segment of the RCA (Figure 1). Results: CAD was present in 10 DM2 patients (5 males, aged 63.1±10.5 years); in 5 DM2 patients (4 males, aged 63±11 years) epicardial coronary arteries were normal. p-FAI was higher in DM2 patients than in healthy controls (p=0.004). The presence of CAD did not impact on p-FAI in DM2 patients, presenting a comparable value (p=0.37). p-FAI was higher in DM2 patients with CAD than in non DM2 patients with CAD (p=0.04). Moreover, p-FAI was higher in DM2 patients without CAD than in non DM2 patients with CAD (p=0.002, Figure 2). Finally, p-FAI was not different in non DM2 patients with CAD compared to healthy controls (p=0.65), suggesting the limited role of CAD in the progression of peri-coronary inflammation when compared to DM2. Conclusions: Coronary inflammation evaluated by p-FAI measurement was higher in DM2 patients, also without CAD. Therefore, our results suggest that DM2 is a determinant of coronary inflammation stronger than CAD. Funding Acknowledgement: Type of funding sources: None.